Hak Ekonomi Istri dalam Pernikahan: Telaah Kritis terhadap Bias Patriarkis dalam Penafsiran Fiqih Klasik - Daroji, Choirul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the concept of nafaqah (spousal maintenance) in Islamic family jurisprudence in response to socio-economic transformations within contemporary Muslim families. The research aims to analyze how classical fiqh constructions assign the obligation of nafaqah exclusively to the husband and to assess the implications of this construction for the economic autonomy of wives. It further seeks to formulate a more equitable framework for Islamic family jurisprudence that is responsive to modern socio-economic realities.Employing a qualitative normative-analytical method, this study analyzes classical fiqh texts across various schools of law, contemporary fiqh scholarship, and Islamic family law studies using the perspectives of maqāṣid al-sharī‘ah and gender analysis. The findings demonstrate that although Islamic law fundamentally guarantees wives’ economic rights through the obligation of nafaqah, dominant interpretations tend to simplify family economic relations and position wives as passive recipients rather than active economic actors.This study argues that the objectives of Islamic law—justice (‘adl) and public welfare (maṣlaḥah)—provide a normative foundation for reconstructing Islamic family jurisprudence toward a model of shared economic responsibility between spouses. It recommends developing fiqh frameworks that recognize economic co-competence based on capacity, contribution, and mutual agreement to promote more egalitarian and just family relations in contemporary Muslim societies